Water Resources Evaluation at City Level Using Weap- the Case of Nablus - Rahmah Othman Khader Abdo (My University, 2009)
Palestinians undergo the problem of insufficient water which emerges largely from the fact that the Israelis do not allow the Palestinians a full control of their water resources. In addition to this restriction, the Palestinians are not permitted to pump out sufficient quantities from the aquifers. This has led to water shortage and thus the majority of the major cities and communities in the West Bank encounter challenges and difficulties in water allocation and management. The City of Nablus is an example of such a situation since it suffers from water shortage and difficulties in distributing water to all users at sufficient quantities. This work utilizes the Water Evaluation And Planning Tool (WEAP) in assessing the management options the Municipality of Nablus is considering for dealing with the on-going water crisis in the City of Nablus. The study methodology consists of three components: data gathering; knowledge acquisition on WEAP and its applications; and WEAP modeling that aided to evaluate water resources management options for Nablus City. The results show that the unmet water demand will continue to increase over the coming years. This is mainly due to the increase in population with limited water resources. Therefore, securing additional water supplies becomes an essential issue to meet the increase in water demand. The most effective option for the period 2009-2025 is the construction of Sabastia well that leads the lowest unmet water demand during this period. The development of new groundwater wells is very efficient in covering the unmet water demand. In this option the unmet water demand will start to decrease when adding the first well in 2015, and more decrease in 2020,2025, and 2035 when the second, the third, and the fourth wells are constructed. The decrease in 2025 in the unmet water demand is more than Sabastia well option, so in this period this option becomes more effective than Sabastia well option. The option of using storm water harvesting gives satisfactory results in decreasing the unmet water demand better than the options of spring rehabilitations and the reduction in water leakage which gives a small decrease in the unmet water demand. Improving the water related infrastructure of the City to decrease the water leakage is crucial in mitigating the water shortage.

يعاني الفلسطينيون من نقص حاد لمصادر المياه نتيجة للقيود التي فرضها الاحتلال الإسرائيلي على الفلسطينيين والتي تعوق دون تطوير مصادر جديدة و تحد من توفر المياه للفلسطينيين . وتفتقر الضفة الغربية لبنية تحتية جيدة لتوفير المياه مما تسبب في فقدان كميات كبيرة من المياه بالإضافة إلى عدم توفر الدعم المالي لمشاريع جديدة، بالتالي بعض المدن الرئيسية في الضفة الغربية كمدينة نابلس تعاني من مشكلة في توزيع المياه إلى المستهلكين بكميات كافية. في هذه الدراسة لتقييم الخيارات لدى بلدية نابلس لتقليل الفجوة بين WEAP تم استخدام برنامج الطلب والتزود. تكونت منهجية الدراسة مما يلي: ( 1) جمع البيانات اللازمة ( 2) التدريب على و تطبيقاته ( 3) نمذجة نظام مصادر المياه في مدينة نابلس باستخدام برنامج (WEAP) برنامج بهدف محاكاة الواقع لدراسة و تقييم الخيارات المختلفة . (WEAP) تشير النتائج التي حصلنا عليها أن الطلب على المياه يتزايد بتزايد عدد السكان على مدى سنوات الدراسة، وإذا استمر الوضع الحالي بوجود نفس كميات المياه فان الفجوة بي ن مقدار التزود و الطلب على المياه سوف تزداد اتساعا. لذا تطوير مصادر إضافية أصبحت حاجة ملحة لمواجهة الطلب المتزايد للمياه، و أيضا استغلال الحصاد المائي و تحسين البنية التحتية للمدينة لتقليل الفاقد من المياه من الأمور المهمة لتقليل الفجوة بين التزود و الطلب.
WEAP - تقييم إدارة التزويد للمياه في مدينة نابلس باستخدام برنامج